ABO blood types as a risk factor for severe symptoms of COVID-19 infection - Al-Hussaniy, Hany A.; Tawfeeq, Karam Turath; Alburghaif, Ali H. (Current Issues in Pharmacy and Medical Sciences, 2026)
Numerous studies have investigated whether the ABO blood group system influences susceptibility to SARS-CoV-2 infection and disease severity. The association between blood type and COVID-19 is thought to involve both genetic and environmental factors. The present study aimed to evaluate the relationship between ABO blood phenotypes and the severity of COVID-19 among Arab populations, with a particular focus on Iraqi patients. To assess the association between ABO blood phenotypes and the occurrence and severity of SARS-CoV-2 infection. A total of 731 patients with COVID-19 confirmed by a positive PCR test were included in the study. A control group consisted of healthy volunteers with negative PCR results and no clinical symptoms of COVID-19. In all participants, ABO blood phenotype was determined. In infected patients, disease severity and mortality were evaluated and analyzed in relation to blood group phenotype. Patients with blood group A demonstrated a higher risk of COVID-19 infection compared with non-A blood groups. In contrast, individuals with blood group O showed a significantly lower incidence of COVID-19 infection and reduced disease severity (odds ratio [OR] = 0.686; 95% confidence interval [CI]: 0.521-0.902). No statistically significant differences were observed for other blood groups. Among critically ill patients, blood group A was associated with a significantly higher mortality rate compared with non-A blood groups (OR = 3.341; 95% CI: 1.416-8.158). Blood group A is associated with an increased risk of severe COVID-19 manifestations, including pneumonia and mortality, whereas blood group O appears to confer a protective effect against severe disease.